Tracing livelihood transition through tourism: A qualitative analysis of Hunza Valley in the post-Karakoram Highway era using the Sustainable Livelihood Framework for Tourism - Sunana Alam (Department of Sociology, Faculty of Social Sciences, Gorontalo State University, Indonesia, 2026)
This study examines how construction of the Karakoram Highway (KKH) has influenced the livelihoods of residents in Pakistan’s Hunza Valley (HV) through tourism growth, using the Sustainable Livelihood Framework for Tourism (SLFT). Although transport infrastructure such as the KKH can generate economic opportunities, these effects remain underexplored in the literature from a localized and multidimensional livelihood perspective, particularly in tourism contexts. Using a qualitative design, the study draws on in-depth interviews and field observations to assess changes in human, social, natural, physical, financial, institutional, and informational assets associated with the KKH and subsequent tourism expansion. Fifteen semi-structured interviews were conducted between June and September 2025 and were complemented by systematic field observations in central, lower, and upper Hunza. The findings indicate that while the KKH has expanded economic opportunities, it has also created trade-offs across livelihood capitals; for example, financial gains have often been accompanied by pressures on natural and cultural assets. Notably, the study identifies information capital as a critical emerging resource that enables residents to increase tourism-related income, attract visitors, and adapt to rapidly changing market dynamics. Consistent with prior SLFT-based research, community responses vary depending on social relations, resource availability, and gaps in policy implementation. Sustainable livelihood outcomes therefore require tourism planning that meaningfully involves local communities and policies that balance economic development with cultural sustainability and environmental protection. The study contributes to tourism scholarship on mountainous regions and offers recommendations for infrastructure development that is sensitive to local livelihood patterns in developing economies.